1984
DOI: 10.11606/issn.2526-3358.bolzoo.1984.122170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variation of salinity on protein, RNA and DNA contents of liver, muscle and ovary of female singi fish, heteropneustes fossilis (Bloch), at two phases of reproductive cycle

Abstract: Depa r t m e n t of A n i m a l Physiology, Bose Institute, P-l/12, CIT Sche me VII M, K a n k u r g a c h i , C a l c u t t a 700054. ( recebido em 1 6 . I X . 1983) RESUMO -Investi g o u -s e as mudanças causadas nos teores de p r o t e í n a s je ácidos n u c l e i c o s do fígado, m úsculo, ovários e peso dos orgãos (HSI, GSI) pela v a r i a ç ã o de sali n i d a d e do meio (65, 135 e 225_mOsm, NaCl / l i t r o^ e salin i d a d e zero ou á gua destilada) em fêmeas nao vit e l o g e n i c a s (NV) e^v i t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studies of saline exposure up to 4ppt reported an increase in GSI as well as RNA and DNA content of ovary of H. fossilis (Dasmahapatra & Medda, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of saline exposure up to 4ppt reported an increase in GSI as well as RNA and DNA content of ovary of H. fossilis (Dasmahapatra & Medda, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…There was an increase in diameter of certain stages of oocytes (CNO, EPNO) in this study only with short‐term saline exposure (8 days). Studies of saline exposure up to 4ppt reported an increase in GSI as well as RNA and DNA content of ovary of H. fossilis (Dasmahapatra & Medda, ).…”
Section: Discussionmentioning
confidence: 99%